Silent Luxury di Alam Tropis:Mangrove Forest Bathing sebagai Produk Wellness Tourism Berbasis Pengalaman Sensorik - Muhammad Sobri Maulana; Dwitia Pratiwi; Arditya Prayogi (Jurnal Penelitian Ilmu Pariwisata, 2026)
This study aims to develop a conceptual model for a silent luxury-themed wellness tourism product in a mangrove ecotourism destination through sensory-based forest bathing. The study is grounded in the growth of the global wellness economy, Indonesia's quality tourism agenda, and previous findings indicating that Munjang Mangrove Ecotourism offers a suitable landscape for forest bathing. The method combines a guided narrative literature review examining numerous journal articles, industry reports, and policy documents on wellness tourism and forest bathing, analysis of secondary data from global and national market reports, and product design synthesis. The results indicate that silent luxury can differentiate the product by offering silence, digital pauses, sensory depth, limited group size, and psychological restoration rather than expensive physical facilities. The novelty lies in integrating forest bathing, five-sense experience design, evidence-based wellness indicators, and low-impact ecotourism governance. Wellness claims are framed as restorative experiences that require validation through pilot projects, pre-post surveys, and willingness-to-pay studies.